2019
DOI: 10.2480/agrmet.d-18-00049
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of drought conditions over major maize producing provinces of South Africa

Abstract: In this study, two commonly used drought indices; the Standardized Precipitation Index SPI and Standardized Precipitation Evapotranspiration Index SPEI , were analyzed in order to understand the impacts of drought on maize yield over four main maize production provinces of South Africa. The drought was characterized using three Drought Monitoring Indicators DMI i.e., the Drought Duration DD , Drought Severity DS , and Consecutive Drought Months CDM . The results indicate that maize yield is significantly affec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 36 publications
0
6
0
Order By: Relevance
“…In South Africa, the SPI drought index has been used to study drought characteristics at different timescales [13,15,16,[34][35][36][37] at national and regional level. Studies by [13,15] focused on drought characteristics in the Free State and North West as well as in the Western Cape provinces, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…In South Africa, the SPI drought index has been used to study drought characteristics at different timescales [13,15,16,[34][35][36][37] at national and regional level. Studies by [13,15] focused on drought characteristics in the Free State and North West as well as in the Western Cape provinces, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…It had been shown that the SPEI shown a consistent performance in drought monitoring in Pakistan compared to 15 various drought indices 35 . In a recent study by Omolola et al 36 for 4 major maize producing South African provinces (identical to the study area used in this study) discovered that the SPEI-3, calculated based on meteorological data from 27 ground stations, was significantly correlated with maize yield during the growing season from 1990 to 2015. Supported by this result, this study adopts drought analysis based on SPEI 3-month time scales.…”
Section: Introductionmentioning
confidence: 59%
“…The SPEI considers the effect of potential evapotranspiration (PET) using the FAO-56 Penman–Monteith equation, thereby representing a simple climatic water balance. In this study, we used the 3-month time scale SPEI data set (SPEI-3) 36 . The time window was set in parallel with the HMD time window (5-months) to capture the yield variability due to drought stress.…”
Section: Methodsmentioning
confidence: 99%
“…While these indices have been extensively employed in various studies, our approach diverges significantly in its utilization of these indices. Contrary to the conventional use of default timescales in previous studies [19,35], this research strategically categorizes these timescales (3 and 6-month timescales) into specific seasons. This categorization is carefully aligned with the various stages of the maize growing season-computing, identifying, monitoring and characterizing droughts aids in developing and implementing drought management and mitigation strategies.…”
Section: Introductionmentioning
confidence: 99%